2009
DOI: 10.1093/bja/aep279
|View full text |Cite
|
Sign up to set email alerts
|

Goal-directed haemodynamic therapy and gastrointestinal complications in major surgery: a meta-analysis of randomized controlled trials

Abstract: Postoperative gastrointestinal (GI) dysfunction is one of the most frequent complications in surgical patients. Most cases are associated with episodes of splanchnic hypoperfusion due to hypovolaemia or cardiac dysfunction. It has been suggested that perioperative haemodynamic goal-directed therapy (GDT) may reduce the incidence of these complications in cardiac surgery, and other surgery, but clear evidence is lacking. We have undertaken a meta-analysis of the effects of GDT on postoperative GI and liver comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
187
0
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(203 citation statements)
references
References 58 publications
(50 reference statements)
7
187
0
9
Order By: Relevance
“…Many reports indicate that intraoperative management based on GDT improves patient outcomes [2] [3] [4]. GDT reduces the incidence of postoperative complications and mortality; therefore, the benefit of GDT seems to be established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many reports indicate that intraoperative management based on GDT improves patient outcomes [2] [3] [4]. GDT reduces the incidence of postoperative complications and mortality; therefore, the benefit of GDT seems to be established.…”
Section: Discussionmentioning
confidence: 99%
“…In 2001, a randomized controlled trial (RCT) in patients with severe sepsis demonstrated that the mortality rate was significantly reduced in patients receiving GDT [1]. This approach has also been applied to the management of surgical patients under general anesthesia, and it has been reported that GDT may improve patient outcomes by reducing the length of hospital stay (LOS) and the incidence of complications [2] [3] [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(24)(25)(26) On the other hand, in high-risk patients, target driven post-operative hemodynamic optimization has shown improved gastric mucosa acidosis, and reduced post-operative gastrointestinal complications. (31)(32)(33)(34) In view of the GID impact on the clinical outcomes and costs, studies should be encouraged on this subject. Multi-modal approaches, including measures to reduce the mechanic trauma, early mobilization and enteral feeding, more accurate volume replacement and treatment of shock with visceral region monitoring should be investigated in prospective multicenter trials.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a meta-analysis of 26 RCT on patients undergoing major surgery demonstrated that GDT initiated in the perioperative period confirmed the reduced risk of post-operative infections (6). Likewise, early initiation of haemodynamic optimization reduces the risk of postoperative acute renal injury and gastrointestinal complications following major surgery (3,4).…”
mentioning
confidence: 99%